Implementation of collaborative teaching for the College of Computing, Informatics and Mathematics, Universiti Teknologi MARA: a case study of semester 20222 and semester 20224 / Nurzalina Harun ... [et al.] - Harun, Nurzalina; Abd Halim, Suhaila; Sulaiman, Hanifah; Mohd Ariff, Nor Zaina Zaharah; Sadikin, Zubaidah; Mazlan, Mazwani Ayu; Zainol, Zarina (UiTM Press, 2024)
Collaborative teaching allows lecturers to move away from the traditional model of one teacher stirring the entire class. This strategy encourages the integration of different perspectives and teaching styles. As a result, students receive a more thorough and well-rounded education. This method of teaching involves teachers complementing each other’s skills, knowledge, and teaching methodologies. In this article, we describe the implementation of collaborative teaching for two academic terms: semester 20222 (March – August 2022) and semester 20224 (October 2022 – February 2023) for the College of Computing, Informatics, and Mathematics (CCIM), Universiti Teknologi MARA (UiTM) Shah Alam. Respondents from survey data were selected CCIM lecturers collected from three (3) schools of CCIM lecturers, namely which are the School of Computing Sciences, the School of Mathematical Sciences, and the School of Information Science. The survey data collected was mainly , on their experience as well as their evaluation of conducting collaborative teaching during their teaching sessions. The findings were are analyzed in order to make informed decisions for future academic terms. Additionally, recommendations for improvements and best practices were will be suggested based on the feedback received from the respondents.